Eosinophilic enterocolitis: A rare nosological entity - Krati, K; Lemfadli, Y; Boujguenna, I; Rais, H (Bangladesh Journal of Medicine, 2021)
Eosinophilic enterocolitis is an exceptionally rare disease with few cases described in the literature. It is the least frequent manifestation of the broad spectrum of gastrointestinal eosinophilic diseases. We describe a case of a female patient presenting with a form of the disease manifested by Koenig’s syndrome and diarrhea. This posed a diagnostic challenge for us due to its non-specific symptoms, associated with the absence of standardized histological criteria, hence the need for a high level of suspicion. There is also no consensus regarding the treatment. It should be individualized according to the age of the patient and the severity of symptoms. Bangladesh J Medicine January 2021; 32(1) : 65-68